Z problematyki początków szkolnictwa średniego w Oświęcimiu - Chrząszcz, Czesław (Analecta Cracoviensia, 2013)
The article reconstructs the events connected with the beginning years of the grammar school in Oświęcim (today’s Konarski Secondary School). The work of Feliks Tobiczyk, the founder of the school who came from Oświęcim and was a professor in the grammar school in Łańcut, is also reconstructed in the article.The foundation of the grammar school in Oświęcim had a few stages. At the beginning (presumably in December 1914) the grammar school courses were set up in order to satisfy the temporary needs of a huge number of pupils who were escaping from the Russian and left their home schools. 29th January 1915 is the first certain date in the history of the courses. On that day fr. Karol Szałaśny, the parish priest in Oświęcim, sent a letter (which was discovered by the author of the article) to the consistory in Kraków asking them to assign a religion teacher to the school headed by Tobiczyk.The success of the grammar school courses as well as the appeals of the local community made Tobiczyk decide to found a full secondary school in Oświęcim. He devoted himself to the foundation of the school in September 1916 and headed it at his own cost until 1919. Then the school was taken over by Secondary School Society in Oświęcim.